2006
DOI: 10.1111/j.1365-2648.2006.03805.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics education in the nursing profession: literature review

Abstract: Whilst areas of good performance were revealed, many studies identified gaps in professional competence and/or education. New initiatives are underway to support genetics education and its integration into professional practice, but further research is needed on the most effective forms of educational delivery, and an international collaborative approach to this should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 44 publications
0
38
0
2
Order By: Relevance
“…Learning strategy can be applied, for example lecture on genetic topics, workshop participation, and conference on genetics and nursing clinical practice related to genetics (Hsiao et al, 2013;Maradiegue et al, 2005). Integration of genetics into a discussion of the nursing education curriculum for bachelor students were responded positively (Burke & Kirk, 2006;Hetteberg & Prows, 2002;Horner, Abel, Taylor, & Sands, n.d.;Maradiegue et al, 2005;Williams et al, 2011). Discussion of genetics that can be integrated into the curriculum of basic nursing education has been delivered by Jenkins in 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Learning strategy can be applied, for example lecture on genetic topics, workshop participation, and conference on genetics and nursing clinical practice related to genetics (Hsiao et al, 2013;Maradiegue et al, 2005). Integration of genetics into a discussion of the nursing education curriculum for bachelor students were responded positively (Burke & Kirk, 2006;Hetteberg & Prows, 2002;Horner, Abel, Taylor, & Sands, n.d.;Maradiegue et al, 2005;Williams et al, 2011). Discussion of genetics that can be integrated into the curriculum of basic nursing education has been delivered by Jenkins in 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have identified deficits in the genetic skills and knowledge base amongst nurses in a variety of settings [4,27], despite the development of guidelines and efforts to integrate genetics into the nurse educational curriculum [13,22,29]. The ability to identify patients who may benefit from genetic assessment has been described as a key nursing competency, and in the palliative setting, one that may determine whether or not this limited opportunity is seized [22].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Bu gelişmeler, bir yandan tüm dünyada birey, aile ve toplumlar için yeni sağlık hizmetleri fırsatı sunarken, diğer yandan hemşire ve sağlık personeline yeni roller yüklemiştir. [4,5] Genetik alanındaki gelişmelere paralel olarak değişen ve gelişen sağlık bakım hizmetleri tüm disiplinlerde olduğu gibi hemşirelik disiplini içerisinde de heyecan verici yeni bir boyut olarak yerini almaya başlamıştır. [6] Onkoloji, gastroentereloji, pediatri, prenatal taramalar ve yenidoğan taramaları ile ilgili genetik gelişmeler ilgili alanlarda hizmet sunan hemşirelerin klinik uygulamalarını etkilemektedir.…”
Section: Introductionunclassified
“…[7][8][9] Bu gelişmeler, özellikle onkoloji alanında çalışan hemşirelere, genetik gelişmeleri takip etme ve klinik uygulamalarına temel oluşturacak genetik ve genomik bilgiye sahip olma sorumluluğunu yüklemiştir. [5,10,11] Hasta ve ailesinin yanı sıra, koruyucu sağlık hizmetlerinin sunumunda sağlıklı bireylere de bakım veren sağlık ekibinin önemli bir üyesi olarak hemşirelerin, hem maliyet etkin hem de kaliteli bir bakım sunmak amacıyla bilimsel ve teknolojik gelişmeleri takip etmeleri ve sahip oldukları kaynakların farkında olmaları gerekmektedir. [9,12] Hemşireler bireyin, ailenin ve toplumun fiziksel ve psikososyal iyilik halinin sürdürülmesini amaçlayan sağlık hizmetlerinin, tüm alanlarında görev almaktadırlar.…”
Section: Introductionunclassified